The Urgency of Regulating Anti-Circumvention Rules in Indonesia and ASEAN: The Case of Alleged Circumvention of Indonesian Refined Sugar to Vietnam - Fasri Dimas Kristian Pramono; Huala Adolf; Purnama Trisnamansyah (Dinasti Research, 2026)
This study examines how the absence of anti‑circumvention rules in ASEAN and Indonesia weakens the effectiveness of anti‑dumping measures, as seen in the case of alleged circumvention of Indonesian refined sugar to Vietnam. The purpose of this study is to determine the implications of the absence of anti‑circumvention rules in ASEAN on the circumvention of anti-dumping measures as seen in the Indonesia–Vietnam case, and to determine the urgency of regulating anti‑circumvention rules in ASEAN in an effort to prevent the circumvention of anti‑dumping measures in Indonesia and ASEAN. The research method used is normative juridical, coupled with a case study of the alleged Indonesia–Vietnam circumvention, as well as a comparative study of various anti‑circumvention legal instruments in Vietnam, the European Union, and the United States. The results show three main implications. First, legal uncertainty over Vietnam’s unilateral measures; Second, procedural fragmentation that hinders cooperation; and third, the failure to set a binding precedent. The comparative study shows that clear regional rules (clear definitions, objective testing, structured procedural standards, exemptions for genuine operators, and strengthened rules of origin) enhance legal certainty while limiting the abuse of measures. The conclusion that can be drawn is that ASEAN needs to immediately regulate anti‑circumvention rules, along with strengthening rules on origin certification. Gradual implementation at the intra‑ASEAN level will build regional habits and common ground, protect domestic industries, and reduce legal and trade friction.